Problem of industrial injuries in Ukraine - Nesterenko, Oleksandr (National Technical University "Kharkiv Polytechnic Institute", 2025)
The relevance of this work is due to the high level of industrial injuries and the low standard of living indicators in Ukraine compared to the industrialized countries of the European Union. Therefore, the issue of the survival of victims of accidents and occupational diseases is particularly important. This paper collects statistical data from open information sources, based on which some indicators of social protection for victims of accidents and occupational diseases in the workplace are calculated. The dynamics of changes in the number of accidents and occupational diseases in Ukraine from 2007 to 2023 are analyzed. Based on the analysis of the results, the socio economic consequences of reforms in social protection for work-related victims are determined, and measures to reduce the injury rate at enterprises under the conditions of hostilities, population migration, etc., are proposed.
Keywords: accidents; occupational diseases; industrial injuries; state insurance.